Pain Improvement After Healing Touch and Massage in Breast Cancer: an Observational Retrospective Study - Gentile, PhD, Danielle; Boselli, MS, Danielle; Yaguda, MSN,RN, Susan; Greiner, PhD, PA-C, Rebecca; Bailey-Dorton, MD, MSPH, Chasse (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Healing Touch (HT) and Oncology Massage (OM) are nonpharmacologic pain interventions, yet a comparative effectiveness study has not been conducted for pain in breast cancer. Purpose: This breast cancer subgroup analysis compared the effectiveness of HT vs. OM on pain. Setting: The research occurred at an outpatient setting at an academic hybrid, multi-site, community-based cancer institute and Department of Supportive Oncology across four regional locations. Participants: Breast cancer outpatients along the cancer continuum who experienced routine clinical, nonexperimentally manipulated HT or OM. Research Design: The study was an observational, retrospective, comparative effectiveness post hoc subanalysis of a larger dataset. Patients reporting pain < 2 were excluded. Pre- and posttherapy pain scores and differences were calculated. Logistic regression modeled posttherapy pain by modality, adjusting for pretherapy pain. The proportions experiencing ? 2-point (clinically significant) pain reduction were compared with chi-square tests. Intervention: The study focused on the first session of either HT or OM. Main Outcome Measures: Pre- and posttherapy pain (range: 0 = no pain to 10 = worst possible pain). Results: A total of 407 patients reported pre- and posttherapy pain scores, comprised of 233 (57.3%) who received HT and 174 (42.8%) who received OM. Pretherapy mean pain was higher in HT (M=5.1, ± 2.3) than OM (M=4.3, ± 2.1) (p < .001); posttherapy mean pain remained higher in HT (M=2.7, ± 2.2) than OM (M=1.9, ± 1.7) (p < .001). Mean difference in pain reduction was 2.4 for both HT and OM. Both HT (p < .001) and OM (p < .001) were associated